The Effectiveness of Cooperative Learning in Enhancing Students’ Learning Interest in Islamic Religious Education: Evidence from Junior High School in Cirebon, Indonesia - Ramadhanty, Dhara Pramesthi; Umihani, Umihani; Maksum, Ali; Hasbullah, Hasbullah; Mastoah, Imas (Journal of Asian Islamic Educational Management (JAIEM), 2025)
This study aims to test the effectiveness of the Cooperative Learning model in increasing students' interest in Islamic Religious Education in grade 7 of State Junior High School 14 Cirebon. The background of this study is the low interest in learning due to the dominance of monotonous conventional learning methods. The research method uses a quantitative approach with a pre-experimental one-shot case Study type design. The research sample of 35 students was selected through a simple random sampling technique. Data collection techniques include observation, Likert scale questionnaires, and documentation. The validity and reliability of the instrument were tested using the SPSS application. Data analysis was conducted using the Pearson Product-Moment correlation test, the coefficient of determination (R²), and the t-test. The study results indicate a powerful relationship between the application of the Cooperative Learning model and students' interest in learning, with a correlation value of 0.864 and an influence contribution of 74.6%. This study provides practical implications for teachers in increasing student participation and learning motivation through a collaborative and enjoyable learning approach.